EFEKTIVITAS IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DI SEKOLAH DASAR: TINJAUAN OTONOMI, PARTISIPASI MASYARAKAT, DAN PERAN TEKNOLOGI DIGITAL - Agung Gede Agung; Chindytia; Ketut Aris Adi Saputra, I; Edi Adnyana, Putu; Purwadi Putra, I Putu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
School-Based Management (SBM) is an educational management approach that gives schools greater authority to manage their resources. This systematic literature review aims to evaluate the implementation of SBM in elementary schools, focusing on school autonomy, community involvement, and financial transparency and accountability. The literature search was conducted through Google Scholar, Garuda, and SINTA for publications from 2022–2026. The study results indicate that SBM can improve learning quality, budget efficiency, and community collaboration. Successful implementation is supported by effective principal leadership and teacher professionalism. However, limitations in managerial capacity, budget constraints, and community participation remain obstacles. The use of digital technology helps improve transparency and accountability in school management.